2014 IEEE Conference on Control Applications (CCA) 2014
DOI: 10.1109/cca.2014.6981380
|View full text |Cite
|
Sign up to set email alerts
|

On the maximum entropy property of the first-order stable spline kernel and its implications

Abstract: A new nonparametric approach for system identification has been recently proposed where the impulse response is seen as the realization of a zero-mean Gaussian process whose covariance, the so-called stable spline kernel, guarantees that the impulse response is almost surely stable. Maximum entropy properties of the stable spline kernel have been pointed out in the literature. In this paper we provide an independent proof that relies on the theory of matrix extension problems in the graphical model literature … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
3
14
0
Order By: Relevance
“…We first formulate the MaxEnt problem solved by the DT SS-1 kernel without Gaussian and uniform sampling assumptions. Then, we extend the result of [11] and link it to our former result: under general sampling assumption, we show that the SS-1 kernel matrix is the solution of a maximum entropy covariance extension problem [12] with band constraints. This results in the well-known tridiagonal structure of the kernel's inverse, which can be also used for efficient numerical implementations [13], [15,Section 5].…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…We first formulate the MaxEnt problem solved by the DT SS-1 kernel without Gaussian and uniform sampling assumptions. Then, we extend the result of [11] and link it to our former result: under general sampling assumption, we show that the SS-1 kernel matrix is the solution of a maximum entropy covariance extension problem [12] with band constraints. This results in the well-known tridiagonal structure of the kernel's inverse, which can be also used for efficient numerical implementations [13], [15,Section 5].…”
Section: Introductionsupporting
confidence: 57%
“…The arguments in [10] were however quite involved, mainly due to the infinite-dimensional nature of the problem and the fact that the differential entropy rate of a generic CT stochastic process is not well-defined. Another recent contribution is [11] where, under Gaussian and uniform sampling assumptions, it is shown that the SS-1 kernel matrix can be given a MaxEnt covariance completion interpretation [12], that is then exploited to derive its special structure (namely that it admits a tridiagonal inverse with closed form representation as well as factorization).…”
Section: Introductionmentioning
confidence: 99%
“…Proof: By Theorem III.2, the maximum entropy completion of Σ (1) n (x) can be recursively computed starting from the maximum entropy completions of the nested principal submatrices of smaller size. The statement can thus be proved by induction on the dimension n of the completion.…”
Section: Maximum Entropy Properties Of the DC Kernelmentioning
confidence: 99%
“…Its derivative with respect to λ is where c is a constant. Now consider the following factorization of the first order stable spline kernel [10]:…”
Section: Part (2)mentioning
confidence: 99%